A hurdle-based learning design effect on locomotion pattern and hurdle clearance kinematic reorganization - Panteli, F.; Theodorou, A.; Smirniotou, A. (Motor control, 2023)
The study assessed the manifestation of a regulated locomotion pattern while clearing the first two hurdles during running. In addition, the effect of a hurdles` learning design, using specific activities and manipulated task constraints, on regulation strategies and kinematic reorganization was examined. Pre- and posttests were conducted. Twenty-four young athletes were randomly assigned into an experimental and a control group, and performed 18 training sessions, consisting of a hurdle-based intervention for experimental participants and a more generalized athletics training for control participants. Different footfall variability curves were recorded, suggesting that young athletes regulated locomotion pattern to clear the hurdles according to their needs. Task-specific training contributed to lower values of variability for the entire approach run and to functional movement reorganization, affording learners to take-off further from the hurdle with a higher horizontal velocity, leading to a more flat hurdle clearance stride and to a significant hurdle running performance improvement.